What The World Can Learn From Sri Lanka's Post-tsunami Experiences - Mulligan, Martin; Shaw, Judith (Penerbit Universiti Sains Malaysia (USM Press), 2007)
When the tsunami devastated communities along two-thirds of Sri Lanka's coast at the end of 2004, the national community rallied impressively and, for a brief period, there was an opportunity to turn a fragile "ceasefire" agreement into an enduring peace settlement. That opportunity was wasted and underlying weaknesses in governance have bedevilled the recovery process. The world must learn from Sri Lanka's difficult experience.